Philosophical Approaches In The Interpretation Of Art (The Peerian Journal, 2025)
The article discusses the philosophical interpretation of art as one of the oldest approaches in the history of mankind, through which we can discover the deep layers of meaning of works of art, understand the artist's worldview, the historical and social context of the work. This approach is a process of understanding art not only through "seeing", but also through "thinking" and "emotional experience"